2018
DOI: 10.1177/0011000018756882
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Social Change: A Qualitative Analysis of Counseling Psychologists’ Engagement in Advocacy

Abstract: In recent years, many counseling psychology training programs in the United States have adopted social justice principles into training. Although previous studies have provided thought-provoking discussions on social justice advocacy, they mostly reflected the voices of psychologists in academia; therefore, the advocacy work of practitioners has been neglected. In order to explore the advocacy experiences of counseling psychologists in practice, we utilized qualitative content analysis to analyze semistructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 37 publications
5
41
0
2
Order By: Relevance
“…With respect to social justice counseling competency, counselors who trained particularly within diverse settings and communities perceived that those experiences were positively aligned with the counseling profession’s values (Hoover & Morrow, 2016) and prepared them to enact positive system‐wide change within their communities (Collins et al, 2015; Crook et al, 2015; Luu & Inman, 2018; Ramirez Stege et al, 2017; Singh et al, 2010). Furthermore, Kozan and Blustein (2018) reported that practitioners who graduated from a socially just–oriented program gained several advocacy behaviors, such as recognizing impacts of systemic factors on mental health, integrating social justice perspectives into case conceptualization and the therapeutic alliance, adopting nontraditional roles to help clients navigate multiple systems, advocating for culturally responsible practices and policies in their organizations, and addressing power dynamics and contextual issues within the profession. With these benefits, trainees and practitioners noted some difficulty moving from microlevel (i.e., awareness‐building) to macrolevel (i.e., systems collaboration) interventions (Ramirez Stege et al, 2017), which may have resulted from navigating personal needs and social justice goals as well as encountering backlash from peers for their social advocacy efforts (Malott, Schaefle, Paone, Cates, & Haizlip, 2019).…”
Section: Scholarship: a Brief Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…With respect to social justice counseling competency, counselors who trained particularly within diverse settings and communities perceived that those experiences were positively aligned with the counseling profession’s values (Hoover & Morrow, 2016) and prepared them to enact positive system‐wide change within their communities (Collins et al, 2015; Crook et al, 2015; Luu & Inman, 2018; Ramirez Stege et al, 2017; Singh et al, 2010). Furthermore, Kozan and Blustein (2018) reported that practitioners who graduated from a socially just–oriented program gained several advocacy behaviors, such as recognizing impacts of systemic factors on mental health, integrating social justice perspectives into case conceptualization and the therapeutic alliance, adopting nontraditional roles to help clients navigate multiple systems, advocating for culturally responsible practices and policies in their organizations, and addressing power dynamics and contextual issues within the profession. With these benefits, trainees and practitioners noted some difficulty moving from microlevel (i.e., awareness‐building) to macrolevel (i.e., systems collaboration) interventions (Ramirez Stege et al, 2017), which may have resulted from navigating personal needs and social justice goals as well as encountering backlash from peers for their social advocacy efforts (Malott, Schaefle, Paone, Cates, & Haizlip, 2019).…”
Section: Scholarship: a Brief Reviewmentioning
confidence: 99%
“…Limitations of previous scholarship include (a) how social justice counseling and social justice counseling competencies are operationalized by practitioners and clients (Ramirez Stege et al, 2017; Schriberg & Clinton, 2016); (b) how social justice competency develops as an aspect of multicultural competency (Crook et al, 2015; Hays, 2008; Presseau et al, 2018); (c) what social justice counseling efforts are enacted by counselors (Malott et al, 2019); and (d) at what levels of intervention, and to what degree, counselors and clients experience social injustice or barriers to social justice work and the impact of those experiences on counseling process and outcome (Crook et al, 2015; Kozan & Blustein, 2018). Hays and Dahl (in press) suggested indicators of MSJCC research effectiveness at the six intervention levels (see Ratts et al, 2016).…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations